Painful knee but not hand osteoarthritis is an independent predictor of mortality over 23 years follow-up of a population-based cohort of middle-aged women. Issue 10 (5th November 2015) - Kluzek, S; Sanchez-Santos, M T; Leyland, K M; Judge, A; Spector, T D; Hart, D; Cooper, C; Newton, J; Arden, N K
Abstract : To assess whether joint pain or radiographic osteoarthritis (ROA) of the knee and hand is associated with all-cause and disease-specific mortality in middle-aged women. Methods: Four subgroups from the prospective community-based Chingford Cohort Study were identified based on presence/absence of pain and ROA at baseline: (Pain−/ROA−; Pain+/ROA−; Pain−/ROA+; Pain+/ROA+). Pain was defined as side-specific pain in the preceding month, while side-specific ROA was defined as Kellgren–Lawrence grade ≥2. All-cause, cardiovascular disease (CVD) and cancer-related mortality over the 23-year follow-up was based on information collected by the Office for National Statistics. Associations between subgroups and all-cause/cause-specific mortality were assessed using Cox regression, adjusting for age, body mass index, typical cardiovascular risk factors, occupation, past physical activity, existing CVD disease, glucose levels and medication use. Results: 821 and 808 women were included for knee and hand analyses, respectively. Compared with the knee Pain−/ROA− group, the Pain+/ROA− group had an increased risk of CVD-specific mortality (HR 2.93 (95% CI 1.47 to 5.85)), while the knee Pain+/ROA+ group had an increased HR of 1.97 (95% CI 1.23 to 3.17) for all-cause and 3.57 (95% CI 1.53 to 8.34) for CVD-specific mortality. We found no association between hand OA and mortality. Conclusion: We found a significantly increased risk of all-cause and CVD-specific mortality in women experiencing knee pain with or without ROA but not ROA alone. No relationship was found between hand OA and mortality risk. This suggests that knee pain, more than structural changes of OA is the main driver of excess mortality in patients with OA.